Pterion and its location for neurosurgical approach: a cadaveric study in Southern Thailand - Kaewborisutsakul, Wilairat; Wirakiat, Wimon; Kaewborisutsakul, Anukoon (Journal of Medicine and Health Sciences, 2022)
Abstract The pterion is a sutural confluence area in the lateral section of the skull where the frontal, parietal, temporal, and sphenoid bones are connected. A knowledge of the exact location and anatomical landmarks of the pterion is crucial in surgical intervention to approach the anterior and middle cranial fossae. Therefore, the present study aims to determine the types and positions of pterion. First, sixty pterions from 30 cadaveric skulls were obtained. Second, the morphology and sutural patterns of the pterion were determined based on Murphy’s classification. The results found that the most common type of pterion among Southern Thai people in this study was the sphenoparietal type, followed by epipteric, frontotemporal and stellate types, respectively. Additionally, this study provided valuable data on the mean distance from the location of the pterion to five external landmarks, including the frontozygomatic suture, the mid-zygomatic arch, the external acoustic meatus, mastoid process, and the zygomatic angle; and two internal landmarks, the sphenoid ridge and the optic canal. All of the results in this study may be important for neurosurgery on the optimal bony aperture when neuronavigation devices are not available, and provide forensic anthropology information for further study.